The Linear Immunoblotting for Screening Antibodies of Class G and M to the Immunodominant Pathogens of TORCH - S. S. Mardanly; V. A. Arsen'eva; M. V. Zaharov; S. G. Mardanly; E. A. Amelina; S. V. Rotanov (Эпидемиология и вакцинопрофилактика, 2015)
It was developed a new kit of reagents «Line-Blot TORCH-profile» to define in the format of linear immunoblotting antibodies to main agents TORCH group (kit N1 - for IgG and kit N 2 - for IgM). In the study of 141 certified controls industrial production showed 100% sensitivity and specificity of studies with a new kit. The study in ELISA and linear immunoblotting with developed set and its counterpart foreign production of clinical samples submitted from persons held diagnostic testing, made it possible to calculate the clinical informativity of both studied methods and corresponding sets of reagents according to GOST R 53022.3-2008. This has led to the recommendation set No.1 (IgG) as an alternative test to the use instead of several ELISA kits for determining monospecific antibodies to each of the major pathogens of TORCH group, and the set No.2 (IgM) - to determine active phase of infection or timing of infection.